Impact of financial stress in~advanced and emerging economies - Flavio César Valerio Roncagliolo; Ricardo Norberto Villamonte Blas (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - The Purpose - of the paper is to examine the differences in the impact of financial stress in advanced and emerging economies. Design/methodology/approach The authors employ a panel vector autoregression model (PVAR) for a comparative analysis of the relationship between financial stress, economic growth and monetary stability in 14 advanced and emerging economies. A homogeneous measure of financial stress is constructed and measured as an index that provides signals of stress episodes in an economy. Findings The impact of financial stress shocks is greater on the economic growth of advanced economies; likewise, financial stress shocks are significant only in advanced economies. The interbank interest rate is negatively affected by financial stress in emerging economies. In general, the results show a clear view of the importance of financial stability and the economic relevance of financial stress measures in the context of macro-prudential regulation. Originality/value The results can be extended to monetary policy to implement measures that mitigate the impact of future financial crises.
Keywords: 330; Economic growth; Financial stress; Inflation; Interest rate; PVAR; Real estate market